Digital Trade Agreements in Shaping E-commerce in the European Union - Yenin, Oleksandr; Shymanska, Kateryna; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis analyses how Digital Trade Agreements (DTAs) influence cross-border e-commerce in the EU, with a focus on SMEs. It is structured around three research questions: whether DTA implementation leads to EU SMEs’ growth in cross-border e-commerce; how effective the EU’s DTAs with Japan and Singapore are in terms of trade facilitation, administrative burden reduction, and SME participation in digital trade; and what gaps and disparities across EU member states and firm sizes still exist in SMEs’ digital readiness. The research combines a qualitative study of provisions in the EU-Japan Economic Partnership Agreement and the EU-Singapore Digital Partnership with descriptive statistics from Eurostat, OECD, WTO, and DSTRI. The results show that DTAs enable data flows, electronic signatures, paperless customs, and consumer protection, and are associated with lower digital trade costs. But, effects are uneven due to weak SME capabilities, regulatory fragmentation, and tensions with EU data and platform regulation, so the findings indicate mechanisms rather than clear causal impacts.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses